Development of Interactive E-Modules Based on POGIL (Process Oriented Guided Inquiry Learning) on Stoichiometry Material in Senior High School - Siti Zahroni; Erdawati; Muktiningsih Nurjayadi (Postgraduate, University of Mataram, 2025)
This research aims to produce a POGIL-based interactive chemistry e-module for chemistry learning in chapter stoichiometry or chemical calculation. This type of research is Research and Development (RnD) and the Borg and Gall development model. The subjects of this research were XI grade high school students. Product validation was carried out by material and language and media experts. The application used is Flip PDF Professional. The product trial was conducted at SMAN 71 Jakarta. The results showed that: (1) Expert assessment related to material aspects amounted to 85% with good interpretation, language aspects 85.83% good interpretation, and media aspects 82.21% good interpretation. (2) Assessment by teachers on a small and large scale as a whole increased, namely 94.91% on a small scale and 99.22% on a large scale with very good interpretation, and assessment by students as a whole also increased, namely 82% on a small scale and 83.50% on a large scale with good interpretation. It can be concluded that the e-module developed is very good and feasible to use as teaching material in the classroom and the students' independent learning process.